HighStitch: High Altitude Georeferenced Aerial Images Stitching for Rocking Telephoto Lens - Yong Zhao (IEEE, 2021)
A georeferenced orthophoto built from aerial images is the basic resource for various of remote sensing applications. As traditional low flight altitude aerial photographic survey is hard to handle large areas, higher altitude brings better survey efficiency, and a telephoto camera is required to maintain the resolution. Since existed structure from motion (SfM) methods are not suitable to process the low field-of-view images with high altitude, this article presents a novel georeferenced orthophoto stitching solution for telephoto images, which contain both translation and rotation movements. A mission planning strategy is designed to guarantee the consistent quality, according to the flight plan and camera intrinsic parameters. The potential matching topology is obtained by projecting images to the prior ground plan,e and overlap scores are estimated for neighbors query, followed with a feature-based keypoint matching. The ground plane and camera poses are optimized by joint considering feature matches, GPS and gimbal rotation information, while the final orthophoto is fused with a fast exposure leveling and weighted multiband-blending algorithm. The experiments show that our system is able to output novel quality orthophoto with high robustness, and we shared a trial version of our algorithm.1